PERMEABILTY OF AN ORGANO-MODIFIED BENTONITE TO ETHANOL-WATER SOLUTIONS - Gates W.P.; Nefiodovas A.; Peter P. (My University, 2004)
Permeability is often the limiting factor in clay-based barrier systems designed to attenuate miscible or immiscible contaminant transport. One critical aspect of barrier design is prediction of the effects of permeant conditions on physicochemical properties (e.g swelling) of the clay component and thus ultimately, the permeability of the barrier. To this end, the permeability of an organically modified bentonite to ethanol-water solutions was determined to approximate the effects of organo sorption-induced swelling. The bentonite was modified with a substituted alkylammonium cation: benzyloctadecyldi-methylammonium (BODMA). Powder X-ray diffraction (XRD) measurements were used to measure interlayer expansion and to estimate aggregate particle densities at any given ethanol concentration. Permeability measurements were conducted on samples under confining overburden stresses of 43 kPa (~2.5 m of saturated soil) using a hydraulic gradient of ~300. Sample thickness was continuously monitored during measurements of volumetric flow so that sample strain, void ratio and porosity could be calculated from changes in sample pore volumes. For calculations of porosity and void ratio, the swelling solid volume, determined from XRD, was assumed to include the sorbed layer (crystalline water/ethanol), the thickness of which is not normally considered in engineering applications. Exposure of the BODMA bentonite to increasing ethanol concentrations increased the swell volume of the clay. Measured coefficients of permeability for the BODMA bentonite decreased from ~1610 À7 m s À1 for pure water to ~8610 À10 m s À1 for pure ethanol. Exposure of the organo clay to ethanol-water solutions containing 0.2 M NaCl increased the effect of ethanol on clay swelling and permeability. Probable consequences of the effects of sorption-induced swelling on permeability and the performance of organo clay-based permeable reactive barriers are discussed.
Keywords: Bentonite